Intelligence, Biosecurity and Bioterrorism - Walsh, Patrick F. (Palgrave Macmillan UK, 2018)
This book explores how potential bio-threats and risks may evolve post 9/11 given the rapid changes in biotechnology and synthetic biology. It also explores what role intelligence communities can play in understanding threats and risks. It argues that although bio-threats and risks are largely low probability and high impact in nature, intelligence in 'Five Eyes' countries remain insufficiently prepared to understand them. This book identifies key areas where intelligence reforms need to take place including a more strategic and systematic collaboration between national security/law enforcement intelligence and the scientific community. It is aimed at intelligence analysts, those in the scientific community working on health security threats, policy makers and researchers working on biosecurity and bioterrorism threats and risks.